Effect of rifampicin, isoniazid on acute and subacute inflammation in male Wistar rats: an experimental study - Gandigawad, Priya; Hogade, Anil P.; Patil, P. A.; Malur, P. R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Tuberculosis (TB) is characterized by significant inflammation leading to complications like pulmonary fibrosis, constrictive pericarditis, etc. Drugs possessing anti-inflammatory activity can reduce the complications of infections occurring due to inflammation and fibrosis. To study the effect of rifampicin, isoniazid on acute and subacute models of inflammation in male Wistar rats. Methods: The in vivo anti-inflammatory activity of rifampicin, isoniazid was studied using acute (carrageenan paw edema) and sub-acute (cotton pellet granuloma and histopathologic examination of grass pith) models of inflammation. Results: Rifampicin and isoniazid used in the present study showed significant anti-inflammatory activity in acute as well as subacute models of inflammation. Conclusion: Rifampicin and isoniazid when administered to treat TB can reduce complications of TB by virtue of its anti-inflammatory activity.